The council of mirrors - Buckley, Michael; Ferguson, Peter, 1968- (New York : Amulet Books, 2012)
Hoping to save their family and the citizens of Ferryport Landing from the evil plans of Mirror, Sabrina and Daphne Grimm seek counsel from the other magic mirrors, who advise them to join forces with the Scarlet Hand.
Keywords: Characters in literature -- Fiction; Sisters -- Fiction; Magic -- Fiction; War -- Fiction; Mystery and detective stories